Evaluation of alexithymia in individuals with chronic pain in a Mexican population: Alexithymia in a Mexican population. (May 2021) - Fresán, Ana; González-Castro, Thelma Beatriz; Pool-García, Sherezada; Tovilla-Zárate, Carlos Alfonso; Castellanos-Narvaéz, Eduardo; Cruz, Juan Pablo Sánchez de la; Juárez-Rojop, Isela Esther; López-Narváez, María Lilia; Lopez, Alejandro Molina
Introduction: Alexithymia is the difficulty in identifying and describing feelings. Several studies have suggested that chronic pain can be linked to alexithymia. The aims of this study were to determine the presence of alexithymia in a sample of Mexican individuals who attended public health services, to assess if alexithymia is higher in medically ill individuals with pain than in those without pain, and to determine which alexithymia dimensions are more affected by the presence of pain. Methods: Demographic and clinical features were evaluated in 250 Mexican outpatients of the General Hospital of Comalcalco, Tabasco. Pain was evaluated using the Visual Analogue Scale for Pain Assessment (VAS-P) and alexithymia was evaluated using the Toronto Alexithymia Scale (TAS-20). Results: 38.8% of the sample was identified with probable/definite alexithymia and up to 61.2% of individuals were currently experiencing pain. Individuals with pain exhibited higher scores in the TAS-20 dimensions: difficulty describing feelings (p = 0.02), difficulty identifying feelings (p < 0.001) and higher total TAS-20 score (p < 0.001). Also, Probable/definite alexithymia was more frequently reported in individuals with pain (49% vs. 21.6%, p < 0.001). Conclusions: Our results show that a large proportion of individuals who attend public health services in a Mexican population present pain. We also identified that pain could be associated with alexithymia, in particular with a difficulty in describing and identifying feelings. An early identification and treatment of alexithymia could help in reducing the clinical burden of chronic pain in Mexican outpatients.